Bronchodilator efficacy and safety of indacaterol 150 µg once daily in patients with COPD: an analysis of pooled data - Bleecker ER; Siler T; Owen R; Kramer B (International Journal of COPD, 2011)
Eugene R Bleecker1, Thomas Siler2, Roger Owen3, Benjamin Kramer41Center for Genomics and Personalized Medicine Research and Translational Medicine Institute, Wake Forest University Health Sciences, Winston-Salem, NC, USA; 2Midwest Chest Consultants, Saint Charles, MO, USA; 3Novartis Horsham Research Centre, Horsham, West Sussex, UK; 4Respiratory Development, Novartis Pharmaceuticals Corporation, East Hanover, NJ, USABackground: Indacaterol is an inhaled, once-daily long-acting β2-agonist bronchodilator for regular use in patients with chronic obstructive pulmonary disease (COPD). As indacaterol is the first once-daily β2-agonist to be developed, it is relevant to evaluate its bronchodilator efficacy, safety, and tolerability.Methods: Data were pooled from three randomized, double-blind, clinical studies in patients with moderate-to-severe COPD treated with indacaterol 150 µg qd (n = 627) or placebo (n = 1021). Bronchodilator efficacy was assessed as trough (24-hour post-dose) forced expiratory volume in 1 second (FEV1) after 12 weeks (primary endpoint in individual studies) and FEV1 measured serially post-dose. Rescue use of albuterol was monitored.Results: At week 12, indacaterol increased trough FEV1 by 160 mL compared with placebo (P < 0.001), exceeding the 120 mL level prespecified as clinically important. FEV1 during the first 12-hour post-dose at week 12 averaged 210 mL higher with indacaterol than with placebo (P < 0.001). Patients receiving indacaterol recorded 53% of days without use of rescue albuterol, compared with 38% of days in the placebo group (P < 0.001). Adverse events (mostly mild or moderate) were reported for 52% and 46% of patients receiving indacaterol and placebo, respectively, and serious adverse events for 4% and 5%. Worsening of COPD was the most frequent adverse event (10% indacaterol; 15% placebo). Indacaterol had little effect on pulse or blood pressure or measures of systemic β2-adrenoceptor activity (blood glucose, serum potassium, and corrected QT interval).Conclusion: Indacaterol was an effective bronchodilator and was well tolerated, with a good safety profile over 12 weeks of treatment. It should prove a useful treatment for patients with moderate-to-severe COPD.Keywords: chronic obstructive pulmonary disease, tolerability, inhaled corticosteroids